Prinsip-Prinsip Pemberdayaan Menurut Al-Qur’an (Kajian Tematik Tentang Ayat-Ayat Pemberdayaan Masyarakat) - Abd Wahid (STAI Syaichona Moh. Cholil Bangkalan, 2015)
The benchmarks of human progress lies in civilization.Civilization is the result of work, initiative, and a sense of human life.Humans have always had a tendency to want more and expand. Thiscondition allows humans to perform the empowerment to be more advancedand developed. The Qur'an as a book of guidance for all human beingscontains shari'ah principles that must be executed. However, before thisreligion is accepted by all people (especially Muslims themselves), certainlyneeded measures in order Shari'a religion could actually be done. Steps isthen referred to as measures of empowerment